Internalization of Religious Moderation Values Through Extracurricular Scouts - Agus Samsudin; Supiana Supiana; Nanat Fatah Natsir (Jurnal sosial dan sains, 2023)
Background: This research is based on the phenomenon that occurs that the level of intolerance, tendency to irritability, and excessive attitudes found in madrasah students is still fairly high. In fact, madrassas are places of Islamic education that are oriented towards moderation. Thus, this study seeks to find solutions or strategies to overcome this problem and encourage madrasah students to have a moderate, tolerant attitude, and avoid exaggeration that can damage religious values and life ethics. Purpose: The purpose of this study is to analyze and describe: objectives, programs, implementation, evaluation, supporting and inhibiting factors as well as the success of internalizing the values of religious moderation through extracurricular Scouting in Madrasah Tsanawiyah Assalam, Salem District, Brebes Regency and Madrasah Tsanawiyah Al Irfan Tanjungsari, Sumedang Regency Method: This research is qualitative research using descriptive analytical methods. Data collection techniques are carried out through interviews, observation, and literature. Data analysis is carried out by sorting out the data obtained and then collected for analysis and conclusions. Results: The results of this study show that: 1) the purpose of internalizing the values of religious moderation through extracurricular Scouting at MTs Assalam Salem and MTs Al Irfan Tanjungsari is to produce moderate students 2) the program is realized through scout programs 3) the implementation of the program is realized through concrete steps ranging from the formulation of goals, planning, material selection, human resource involvement, the use of approaches and methods learning, training, and evaluation 4) the evaluation is carried out through process evaluation and evaluation of the success of attitude cultivation 5) the supporting and inhibiting factors consist of internal and external supporting and inhibiting factors 6) the success has a direct and indirect impact. Conclusion: The conclusion of this study confirms that Scouting extracurricular can be an effective means of internalizing the values of religious moderation in the secondary education environment.